Text in Dutch on back: 'American Food and Agricultural exhibition in the RAI at Amsterdam opened by the vice-president of America Mr. Lyndon Johnson ...' - Nijs, Jac. de,
Text in Dutch on back: 'American Food and Agricultural exhibition in the RAI at Amsterdam opened by the vice-president of America Mr. Lyndon Johnson ...'.